The Improving Students Ability in Mathematical Creative Thinking Through Problem Based Learning Model - Reza Handika Winata Lubis (Education Achievement: Journal of Science and Research, 2023)
This research aimed to determine that improving students ability in creative thinking through the PBL model is higher than traditional learning. This research is a quasi experimental research. Sampling method is using random sampling method that is from tenth grade at State Senior High School 7 of Medan selected two classes as sample which subjected to random treatment of one as control class that is X2 and the other as experimental class that is X5. Eksperimental class is utilizing the PBL model and control class is utilizing the traditional learning. Inferensial statistic analysis was performed by Independent Sample t-Test. The math subject is system of linear equations with two variables. Based on the research, it was found that the significance value for mathematical creative thinking ability in the experimental and control classes is 0.038. Because 0.038 < 0.05 then H0 is rejected, So improving students ability in creative thinking the PBL model is higher than traditional learning. It was concluded that improving students ability in creative thinking through the PBL model is higher than traditional learning.